Obtaining and Properties Study of Human Granulocyte-macrophage Colony-stimulating Factor in a Vehicle for Drug Delivery - Esina, T.I.; Shimina, G.G.; Volosnikova, E.A.; Gamaley, S.G.; Danilenko, E.D. (Biomedical Chemistry: Research and Methods, 2024)
Granulocyte-macrophage colony stimulating factor (GM-CSF) is a cytokine that stimulates the growth and development of granulocyte and macrophage progenitor cells. It also increases the activity of mature neutrophils, monocytes, and eosinophils. The preparations of recombinant human granulocyte-macrophage colony stimulating factor (rhGM-CSF) are used to treat the diseases associated with myelosuppression, such as neutropenia of different etiologies, chronic infections, etc. One problem in the widespread use of GM-CSF is its instability in biological fluids, which leads to a short half-life and reduced biological activity. To solve this problem, a method has been developed to incorporate rhGM-CSF into a drug delivery vehicle based on polyglucin. It has been found that the conjugation of rhGM-CSF and polyglucin enhances the resistance of the protein against degradation by trypsin. The dosage form of rhGM-CSF incorporated into the drug delivery vehicle increased the number of segmented neutrophils in CBA mice with cyclophosphamide-induced myelosuppression to a similar extent as the initial rhGM-CSF preparation (300% and 350%, respectively, compared with the control level, 5 days after cyclophosphamide administration). Additionally, it contributed to a more rapid recovery of the total number of bone marrow karyocytes. Thus, a preparation containing a conjugate of rhGM-CSF and polyglucin exerts a more significant effect on activating bone marrow myelopoiesis than the unmodified protein.